Estimating the energy costs of intermittent exercise - Scott, C. B.; Fountaine, C. (Journal of Human Kinetics, 2013)
To date, steady state models represent the only acceptable methodology for the estimation of exercise energy costs. Conversely, comparisons made between continuous and intermittent exercise generally reveal major physiological discrepancies, leading to speculation as to why steady state energy expenditure models should be applied to intermittent exercise. Under intermittent conditions, skeletal muscle invokes varying aerobic and anaerobic metabolic responses, each with the potential to make significant contributions to overall energy costs. We hypothesize that if the aerobic-only energetic profile of steady state exercise can be used to estimate the energetics of non-steady state and intermittent exercise, then the converse also must be true. In fact, reasonable estimates of energy costs to work volumes or work rates can be demonstrated under steady state, non-steady state and intermittent conditions; the problem with the latter two is metabolic variability. Using resistance training as a model, estimates of both aerobic and anaerobic energy cost components, as opposed to one or the other, have reduced the overall energetic variability that appears inherent to brief, intense, intermittent exercise models.